LEXICAL CHARACTERISTICS OF COMPUTER TERMS IN ENGLISH, UZBEK AND KARAKALPAK LANGUAGES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The article is devoted to expose, analyse and study of the structural and semantic characteristics of computer terms in English. The peculiarities of the wordformation process and the functioning of English computer terms are analysed.